Information and communication technologies: where are persons with intellectual disabilities? - Werner, Shirli (Isr J Health Policy Res, 2019)
Individuals with disabilities are entitled to equal access to information and communication technologies (ICT), including the Internet. The study to which this commentary refers has shown that over time (between 2003 and 2015), Internet access by persons with disabilities has increased, but a gap still exists between people with and without disabilities. One population that has been excluded from this study is that of individuals with intellectual disabilities. This is unfortunate because these individuals may face an even greater gap than others in access to the Internet. In this commentary we review the state of ICT use specifically by individuals with intellectual disabilities, and make a few recommendations for future ICT research and for reducing this gap.